Optimalisasi Layanan Pearpustakaan dalam Meningkaatkan Minat Baca Siswa - Anisa Rahmawati (IJAL (Indonesian Journal of Academic Librarianship), 2024)
This research aims to find out how to optimize library services so that they have a good impact in increasing students' interest in reading in an era where many children are addicted to their gadgets, so that the library can become a comfortable and popular place for students. This research method uses qualitative methods, namely research procedures that can produce descriptive data in the form of written and spoken words from people and observed behavior. The results of this research show that first, the services provided by the library are guidance, references, science books in the form of fiction and non-fiction, and complete and comfortable facilities. Second, the development carried out is by continuing to update the reading books in the library so as to create curiosity in children. Third, the guidance provided by the librarian is to continuously remind students by providing a schedule for each day of their class.